Building and Wedging Strategic Alliances: Racial Framing Contests in the Immigrant Rights and Nativist Counter-Movements. (November 2022) - Yazdiha, Hajar
As immigrant rights movements and anti-immigrant mobilizations engage in contentious battles for public support, it is increasingly essential to understand how these opposing political forces develop strategic alliances, garnering power, and shaping larger debates around immigration. Using newspaper data, this study compares case studies of immigrant rights and nativist battles in two mobilizations—the 2012 "No Papers, No Fear Ride for Justice" during the Obama Era and the 2018 "Family Separation Protests" during the Trump Era—to analyze how movements and counter-movements strategically deploy frames to generate or disrupt strategic alliances. Findings identify strategic racial frame deployment as a mechanism that can either amplify or obfuscate racial meanings, enabling, and constraining counter-frames by rival movements. I highlight patterns in how these racial frames are used in framing contests to bring groups together in alliances or wedge groups apart, illuminating the underlying system of racialization as it shapes intergroup boundaries, its limits, and its radical possibilities for transformation.